Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To evaluate [tex]\((m \circ n)(4)\)[/tex], we must first determine the composition of the functions [tex]\( m \)[/tex] and [tex]\( n \)[/tex].
We are given:
[tex]\[ m(x) = 4x - 5 \][/tex]
[tex]\[ n(x) = 2x + 11 \][/tex]
The composition [tex]\((m \circ n)(x)\)[/tex] means substituting [tex]\( n(x) \)[/tex] into [tex]\( m(x) \)[/tex]. This can be written as:
[tex]\[ (m \circ n)(x) = m(n(x)) \][/tex]
Next, we substitute [tex]\( n(x) \)[/tex] into [tex]\( m(x) \)[/tex]:
[tex]\[ m(2x + 11) = 4(2x + 11) - 5 \][/tex]
Performing the multiplication and simplification, we get:
[tex]\[ m(2x + 11) = 4 \cdot 2x + 4 \cdot 11 - 5 \][/tex]
[tex]\[ m(2x + 11) = 8x + 44 - 5 \][/tex]
[tex]\[ m(2x + 11) = 8x + 39 \][/tex]
Now, to evaluate [tex]\((m \circ n)(4)\)[/tex], substitute [tex]\( x = 4 \)[/tex] in [tex]\( m(2x + 11) \)[/tex]:
[tex]\[ (m \circ n)(4) = 8(4) + 39 \][/tex]
[tex]\[ (m \circ n)(4) = 32 + 39 \][/tex]
[tex]\[ (m \circ n)(4) = 71 \][/tex]
We then compare this result with the given options to see if any match:
A. [tex]\((m n)(4) = 8(4)^2 - 6(4) - 55\)[/tex]
B. [tex]\((m n)(4) = 8(4)^2 - 55\)[/tex]
C. [tex]\((m n)(4) = 8(4)^2 + 34(4) - 55\)[/tex]
D. [tex]\((m n)(4) = 8(4) - 55\)[/tex]
Evaluating each:
Option A:
[tex]\[ 8(4)^2 - 6(4) - 55 = 8(16) - 24 - 55 = 128 - 79 = 49 \][/tex]
Option B:
[tex]\[ 8(4)^2 - 55 = 8(16) - 55 = 128 - 55 = 73 \][/tex]
Option C:
[tex]\[ 8(4)^2 + 34(4) - 55 = 8(16) + 136 - 55 = 128 + 136 - 55 = 264 - 55 = 209 \][/tex]
Option D:
[tex]\[ 8(4) - 55 = 32 - 55 = -23 \][/tex]
None of the provided options match the correct evaluation of 71. Therefore, the correct answer is:
[tex]\[ \boxed{\text{No correct option available}} \][/tex]
We are given:
[tex]\[ m(x) = 4x - 5 \][/tex]
[tex]\[ n(x) = 2x + 11 \][/tex]
The composition [tex]\((m \circ n)(x)\)[/tex] means substituting [tex]\( n(x) \)[/tex] into [tex]\( m(x) \)[/tex]. This can be written as:
[tex]\[ (m \circ n)(x) = m(n(x)) \][/tex]
Next, we substitute [tex]\( n(x) \)[/tex] into [tex]\( m(x) \)[/tex]:
[tex]\[ m(2x + 11) = 4(2x + 11) - 5 \][/tex]
Performing the multiplication and simplification, we get:
[tex]\[ m(2x + 11) = 4 \cdot 2x + 4 \cdot 11 - 5 \][/tex]
[tex]\[ m(2x + 11) = 8x + 44 - 5 \][/tex]
[tex]\[ m(2x + 11) = 8x + 39 \][/tex]
Now, to evaluate [tex]\((m \circ n)(4)\)[/tex], substitute [tex]\( x = 4 \)[/tex] in [tex]\( m(2x + 11) \)[/tex]:
[tex]\[ (m \circ n)(4) = 8(4) + 39 \][/tex]
[tex]\[ (m \circ n)(4) = 32 + 39 \][/tex]
[tex]\[ (m \circ n)(4) = 71 \][/tex]
We then compare this result with the given options to see if any match:
A. [tex]\((m n)(4) = 8(4)^2 - 6(4) - 55\)[/tex]
B. [tex]\((m n)(4) = 8(4)^2 - 55\)[/tex]
C. [tex]\((m n)(4) = 8(4)^2 + 34(4) - 55\)[/tex]
D. [tex]\((m n)(4) = 8(4) - 55\)[/tex]
Evaluating each:
Option A:
[tex]\[ 8(4)^2 - 6(4) - 55 = 8(16) - 24 - 55 = 128 - 79 = 49 \][/tex]
Option B:
[tex]\[ 8(4)^2 - 55 = 8(16) - 55 = 128 - 55 = 73 \][/tex]
Option C:
[tex]\[ 8(4)^2 + 34(4) - 55 = 8(16) + 136 - 55 = 128 + 136 - 55 = 264 - 55 = 209 \][/tex]
Option D:
[tex]\[ 8(4) - 55 = 32 - 55 = -23 \][/tex]
None of the provided options match the correct evaluation of 71. Therefore, the correct answer is:
[tex]\[ \boxed{\text{No correct option available}} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.